Psilocybin-assisted neurofeedback for the improvement of executive functions: a randomized semi-naturalistic-lab feasibility study - Enriquez-Geppert, S; Krc, J; O'Higgins, F J; Lietz, M (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2024)
Executive function deficits, common in psychiatric disorders, hinder daily activities and may be linked to diminished neural plasticity, affecting treatment and training responsiveness. In this pioneering study, we evaluated the feasibility and preliminary efficacy of psilocybin-assisted frontal-midline theta neurofeedback (NF), a neuromodulation technique leveraging neuroplasticity, to improve executive functions (EFs). Thirty-seven eligible participants were randomized into an experimental group (n = 18) and a passive control group (n = 19). The experimental group underwent three microdose sessions and then three psilocybin-assisted NF sessions, without requiring psychological support, demonstrating the approach's feasibility. NF learning showed a statistical trend for increases in frontal-midline theta from session to session with a large effect size and non-significant but medium effect size dynamical changes within sessions. Placebo effects were consistent across groups, with no tasks-based EF improvements, but significant self-reported gains in daily EFs-working memory, shifting, monitoring and inhibition-showing medium and high effect sizes. The experimental group's significant gains in their key training goals underscored the approach's external relevance. A thorough study with regular sessions and an active control group is crucial to evaluate EFs improvement and their specificity in future. Psilocybin-enhanced NF could offer significant, lasting benefits across diagnoses, improving daily functioning. This article is part of the theme issue 'Neurofeedback: new territories and neurocognitive mechanisms of endogenous neuromodulation'.
Keywords: Humans; psilocybin; Psilocybin; studie proveditelnosti; neurofeedback; frontal-midline theta; Female; mladý dospělý; dospělí; psychedelics; lidé; cognitive enhancement; exekutivní funkce; Adult; executive functions; ženské pohlaví; Male; Young Adult; Neurofeedback; EEG neurofeedback; Executive Function; Feasibility Studies; mužské pohlaví